Key Elements for E-Learning Success in the Context of the Coronavirus Crisis - Nuphanudin, Nuphanudin; Yosafikri, Rahmahdan Qalbi; Tsaabita, Aldila Nisa Ilmatu; Senduk, Agnes Pratiwi; Iqbal, Muhammad; Ma’rifah, Ainun; Kristiawan, Muhammad (Pascasarjana Universitas KH. Abdul Chalim, 2023)
Using the Analytical Multi-Criteria Hierarchy (AHP) approach and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS), this article seeks to discover crucial success criteria for e-learning during COVID-19 in order to enhance process education. Based on established assessment criteria and multi-channel e-learning methodologies, data was gathered by interviewing 69 e-learning leaders in educational institutions during COVID-19. We discovered that managing technology, assisting management, educating students about the usage of the e-learning platform, and requiring a high level of information technology exchange from the lecturer are all important. Universities, staff, and students have had the biggest influence on online learning during COVID-19. The most useful of the five learning models is blended learning. These findings show that e-learning preparation plays a significant impact in boosting the educational process during the COVID-19 pandemic, regardless of the specific technology used by an educational institution.